The Effect of Debt to Assets Ratio, Debt to Equity Ratio, and Current Ratio on the Stock Price of PT Polychem Indonesia Tbk During the Period 2010-2024 - Shinta Shintia Dewi; Fazhar Sumantri; Theysa Sahlani Pratiwi (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the impact of Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Current Ratio (CR) on the stock price of PT Polychem Indonesia Tbk during the period 2010–2024. The Debt to Assets Ratio is used to measure the extent to which the company finances its assets with debt, providing an insight into the company's credit risk. The Debt to Equity Ratio, on the other hand, measures the company’s ability to repay its debts using its own capital. The Current Ratio is used to assess the company’s ability to meet its short-term liabilities. This research employs a quantitative approach using multiple linear regression analysis, processed using SPSS version 27. The sample consists of 15 years of the company's annual reports, with purposive sampling technique. The results of the analysis show that, partially, none of the three ratios—Debt to Assets Ratio, Debt to Equity Ratio, and Current Ratio—significantly affect the stock price of PT Polychem Indonesia Tbk. The t-values for each variable are 0.806 (DAR), -0.169 (DER), and 0.464 (CR), with significance values greater than 0.05 (0.437, 0.869, and 0.651). These findings indicate that these financial ratios are not sufficient to explain the stock price fluctuations of the company during the period under study, which is likely influenced by other factors beyond these ratios.